Wearable smart devices in cancer diagnosis and remote clinical trial monitoring: Transforming the healthcare applications. Issue 10 (October 2022) - Beg, Sarwar; Handa, Mayank; Shukla, Rahul; Rahman, Mahfoozur; Almalki, Waleed H.; Afzal, Obaid; Altamimi, Abdulmalik Saleh Alfawaz
Highlights: Wearable devices are intelligent tools of 21st century modern healthcare systems. Early diagnosis of cancer is the only key decisive factor to start the drug therapy. Smart devices have potential to dramatically change cancer diagnosis process. Remote clinical trial monitoring using smart devices are newer paradigms of the era. Abstract : During the past two decades, the era of digitalization in pharmaceutical device manufacturing has gained significant momentum for maintaining human health. From various available technologies, internet of things (IoT) sensors are being increasingly used as wearable devices (e.g., smart watches, wrist bands, mobile phones, tablets, implantable pumps, etc.) that enable real-time monitoring of data. Such devices are integrated with smart materials that typically monitor the real-time data (blood pressure, blood sugar, heart and pulse rate, cytokine levels, etc.) to advise patients and physicians. Hence, there has been a great demand for wearable devices as potential tools for remote clinical trial monitoring in cancers and other diseases and they are proving to be very cost-effective.